The Irony in Ang Lee’s Life of Pi - Kriswanda Krishnapatria (LPPM Universitas Bina Sarana Informatika, 2021)
This paper investigates and analyses the irony in Ang Lee’s movie: Life of Pi (2012). Irony is one type of satire figure of speech, a language style that is used as a subtle insinuation and contains statements that are very contradictory or inversely proportional to the existing reality. Furthermore, there are three most commonly used irony in literature, which are verbal, situational, and dramatic. The research method applied is descriptive analytic to describe the meaning and context of irony found in Life of Pi. The conclusion is that Ang Lee’s Life of Pi is full of situational irony, thus makes it fascinating to watch and to discuss. Besides, dramatic irony was also found, and it was applied in order to preserve the audience interest’s, provoke curiosity, and make a contrast between the situation of the characters and the later scene that ultimately unfolded. This paper also shows that the cinematographic aspect related to the analysed narration could dramatically add insightful meanings to the irony.